2018
DOI: 10.12681/jhvms.16421
|View full text |Cite
|
Sign up to set email alerts
|

An overview of sheep farming features and management practices in the region of south western Peloponnese and how they reflect on milk microbial load

Abstract: In this study the demographic features, various farm characteristics and milk quality parameters were investigated in sheep farms (n =128) from the North West Peloponnese region, using a prescreen questionnaire. The interviewed sheep farmers were under the control of the regional milk control laboratory of the Hellenic Milk Organization ELGO «Dimitra», which provided us with the corresponding milk quality data for the first quarter of 2014. Our findings regarding the demographic data demonstrated that 23% of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…3.1 Research product and attribute choice 3.1.1 Feta cheese. Dairy products hold a significant position in the diet of Greek consumers, with relatively low elasticity in terms of selling prices and disposable income (Manolopoulou et al, 2018). In Greece, soft cheeses constitute the majority (74.3%) of cheese production and were the most consumed type of cheese in 2017 (ICAP Group, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…3.1 Research product and attribute choice 3.1.1 Feta cheese. Dairy products hold a significant position in the diet of Greek consumers, with relatively low elasticity in terms of selling prices and disposable income (Manolopoulou et al, 2018). In Greece, soft cheeses constitute the majority (74.3%) of cheese production and were the most consumed type of cheese in 2017 (ICAP Group, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Previous papers reported limited information, for example, only regarding specific practices applied in sheep and goat farms or with narrow geographical coverage. For example, previous studies reported information about management practices performed only in farms in some parts of the country (e.g., island of Lesvos: Kizos et al [ 7 ], Peloponnese: Manolopoulou et al [ 8 ], Central Greece: Perucho et al [ 9 ]); other studies reported information only about farms with specific animal breeds (e.g., sheep of the Friesarta breed: Kominakis et al [ 10 ], sheep of the Chios breed: Gelasakis et al [ 11 ]).…”
Section: Introductionmentioning
confidence: 99%